No-biopsy strategy for coeliac disease is applicable in adult patients: a 'real-world' Scottish experience. Issue 2 (11th August 2022) - Hoyle, Aoisha; Gillett, Peter; Gillett, Helen R; Borg, Reuben; Nottley, Steven; Farrow, Samantha; Elgoweini, Maha; Elhassan, Mohamed; Fletcher, Jonathan; Whannel, Gemma; Gracie, Edel; Morgan, Sarah; et al.
Abstract : Objective: Emergency interim guidance from the British Society for Gastroenterology (BSG) states that a no-biopsy strategy is possible to diagnose coeliac disease (CD) in adults with elevated transglutaminase IgA antibody (TGA-IgA) levels. We aimed to determine if the suggested TGA-IgA ≥10× ULN is safe and robust in making the diagnosis in adult patients in Scotland. We also aimed to establish if any important co-diagnoses would be missed if no biopsy was performed. Method: All positive coeliac serology results for patients aged >15 years in Scotland in 2016 (Grampian 2019) were accessed. Data were collected on demographics, TGA-IgA titres, D1 sampling, histology and macroscopic findings at upper and lower gastrointestinal (GI) endoscopy. Results: 1037/1429 patients with positive serology proceeded to biopsy, of which 796/1037 (76.8%) were diagnosed as CD. A total of 320/322 (99.37%) patients with TGA-IgA ≥10× ULN were diagnosed as CD giving the cut-off a positive predictive value of 99.38%. No significant co-pathology was found at endoscopy in these patients. Conclusion: Our results show that a no-biopsy strategy using a cut-off of TGA-IgA ≥10× ULN is safe to diagnose CD and that no important pathology would be missed. The European Society for Paediatric Gastroenterology, Hepatology and Nutrition 2020 and BSG COVID-19 interim guidelines are applicable to adult patients in Scotland.